EZH2-Inhibited MicroRNA-454-3p Promotes M2 Macrophage Polarization in Glioma - Qi, Bin; Yang, Cheng; Zhu, Zhanpeng; Chen, Hao (Frontiers in Cell and Developmental Biology, 2020)
Glioma is a primary intracranial tumor with high incidence and mortality. The oncogenic role of EZH2 has been reported in glioma. EZH2 inhibited microRNA-454-3p (miR-454-3p) by binding to its promoter in chondrosarcoma cells. Therefore, our study aimed to identify whether EZH2 regulated M2 macrophage polarization in glioma via miR-454-3p. Clinical samples of different grades of glioma and glioma cells were collected and immunohistochemistry and RT-qPCR demonstrated that EZH2 was highly expressed in glioma tissues. Expression of EZH2 was positively correlated with the degree of M2 macrophage polarization in glioma tissues. EZH2 was silenced by lentivirus in glioma cells, which were subsequently co-cultured with macrophages to evaluate its effect on macrophage polarization. miR-454-3p, a down-regulated miR in glioma, was found to be increased after silencing of EZH2. Furthermore, MethPrimer analysis showed that EZH2 silencing inhibited the DNA methylation level of miR-454-3p. Additionally, MS-PCR, dual-luciferase reporter, RIP and RNA pull down assays revealed that miR-454-3p promoted PTEN expression by inhibiting m6A modification through binding to the enzyme YTHDF2. Either inhibition of miR-454-3p or PTEN resulted in promotion of M2 macrophage polarization. Collectively, histone methyltransferase EZH2 inhibited miR-454-3p through methylation modification and promoted m6A modification of PTEN to induce glioma M2 macrophage polarization.